Neurohistopathologicallesions in brains of Indian cattle - SINGH, R; KUMAR, R; SINGH, P P; SINGH, K P; DWIVEDI, P; CHAUHAN, R S (The Indian Journal of Animal Sciences, 2011)
The histopathological baseline data on cattle brain affections are not adequately available in Indian cattle. Therefore, a systematic study on 208 brains of adult cattle was carried out at 12 designated neuroanatoluical sites and 67 subanatomical sites. Grossly, no specific brain lesions were found. On microscopic exaluination, 66/208 (31.73%) brains showed spontaneous cytopathological lesions where no specific history of nervous disorder/signs was reported. The lesions included ischemic neurons (5, 2.40%) , Lafora bodies (1, 0.48%), neuromelanins (1, 0.48%), engorgement of vasculature (9,4.33%), hemorrhages in brain substance (10, 4.80%), vascular mineralization (2, 0.96%), vasogenic edema ofaxonic tracts (1, 0.48%), edema around blood vessels (3, 1.44%), proteinaceous globules in vascular lumen (2, 0.96%), vacuolation of white matter (9, 4.330/0), neuropil vacuolation (4, 1.920/0), perivascular cuffing (9, 4.33%), vasculitis (2, 0.96%), microgliosis (9, 4.330/0), non-suppurative meningoencephalitis (2, 0.96%), suppurative meningoencephalitis (3, 1.44%), leptomeningitis (1, 0.48%), neuronophagic nodule (3, 1.44%), satellitosis (3, 1.44%), astrogliosis (1, 0.48%), oligodendrogliosis (1,0.48%), subependymal gliosis (92, 0.96%), melanin pigmentation of pia mater (1, 0.48%), and parasitic infestations (2, 0.96%). No case of bovine spongiform encephalopathy (BSE) was identified in any of the samples. In the study, no novel histopathological findings were recorded. However, a case of Lafora bodies and mineralization of vessel walls in cattle seem to be the first report in India. It may be concluded that some of these changes in brains of cattle were frequent in occurrence, which may have implication for the pathologists engaged in neuropathology and nervous disease surveillance work.Â